A 17‐year‐old woman with a solitary, mixed squamous cell and glandular papilloma of the bronchus. Issue 2 (30th November 2018) - Saraya, Takeshi; Fujiwara, Masachika; Kimura, Hirokazu; Takei, Hidefumi; Takizawa, Hajime
Abstract : A 17‐year‐old woman was referred to our hospital due to cough on exertion and right chest pain over the previous two months, together with bloody sputum over the previous week. Chest X‐ray demonstrated a nodule measuring 3 cm in diameter in the right middle lung field. On repeated bronchoscopy, the tumour was recognized as a rapidly growing intra‐bronchial protruded tumour at the orifice of the right B8. Based on a tentative diagnosis of lung cancer, right lower lobectomy was performed. She was diagnosed with mixed squamous cell and glandular papilloma of the bronchus without smoking history and human papillomavirus infection. Solitary endobronchial papillomas are rare but should be considered a differential diagnosis for solitary lung nodule with the potential to develop into carcinoma. Abstract : Solitary endobronchial papillomas are extremely rare, accounting for only 0.38% of all lung tumours and approximately 7% of all benign epithelial and mesenchymal lung tumours. Here, we present an unexpected case of mixed papilloma in the youngest known patient to date who suffered from chest pain and bloody sputum.